In-situ alternating-current voltage SHG system and method for representing intrinsic ferroelectric upset thereof

By using the in-situ AC voltage SHG system in the static voltage SHG test, and using choppers and arbitrary signal generators to generate periodic light and AC voltage signals, a method of quickly and accurately characterizing the polarization characteristics of ferroelectric materials is achieved, and the solution is The existing testing methods take time and are affected by external conditions.

CN119470352AActive Publication Date: 2025-02-18XIANGTAN UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411600883.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-18
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

The existing static voltage SHG test method takes too long and is greatly affected by external conditions, so it is impossible to accurately characterize the polarization characteristics of ferroelectric materials.

Method used

Using the in-situ AC voltage SHG system, periodic light is generated through choppers as carrier signals, and any signal generator generates AC voltage signals to realize the amplitude modulation of the optical signal, and the modulated optical signal is converted into electrical signals through the PMT photodetector. , complete the quick test.

Benefits of technology

Completed the test within 300ms, reducing the impact of external conditions on the test results and better characterizing the polarization characteristics of ferroelectric materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119470352A_ABST
    Figure CN119470352A_ABST
Patent Text Reader

Abstract

The invention discloses an in-situ alternating-current voltage SHG system and a method for representing intrinsic ferroelectric upset thereof, and belongs to the technical field of solid-state dielectric application. According to the invention, periodic light generated by a chopper is used as a carrier signal, an AC voltage signal is generated by any signal generator, an SHG signal generated when the AC voltage signal acts on a sample is used as a modulation signal, amplitude modulation of an optical signal is realized, and the modulated optical signal is converted into an electric signal by a PMT photoelectric detector. A photoelectric signal and a carrier signal of the PMT photoelectric detector are simultaneously input into the digital lock-in amplifier and are demodulated and output. The application of the AC voltage and the demodulation output of the PMT photoelectric signal are carried out at the same time through a trigger signal generated by the AWG. Compared with an electrostatic voltage SHG system for representing intrinsic ferroelectric flipping, the method has the advantages that on the basis that polarization flipping of a large leakage current sample can be tested, the test time is shortened, and the influence of external conditions on a test result is reduced or eliminated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field The invention relates to the technical field of solid-state dielectric application, and in particular to an in-situ alternating current voltage SHG system and a method for characterizing intrinsic ferroelectric switching thereof. Background Art Ferroelectric materials are a type of functional materials with spontaneous polarization properties. Because of their stable spontaneous polarization and switchable polarization characteristics under an external electric field, they have broad application prospects in non-volatile ferroelectric memories, pyroelectric infrared detectors, ferroelectric tunneling junctions, field effect transistors, etc. Ferroelectric polarization intensity is an important parameter of ferroelectric materials. It has a direct impact on the performance of ferroelectric devices, and the hysteresis loop obtained by its change with the external electric field can be used as an important basis for whether a certain material has ferroelectricity. Usually, ferroelectric materials are characterized by macroscopic ferroelectric polarization through ferroelectric analyzers, and the curve relationship between macroscopic ferroelectric polarization and applied voltage is established. It has the advantages of simple operation, convenience, and speed, but it will be affected by leakage current during the test process. Ferroelectric materials can also be characterized by using piezoelectric force microscopy (PFM) to characterize the ferroelectric polarization performance of micro-areas, and test the domain reversal state of ferroelectric materials in different areas and different voltages. It has the advantages of real-time testing and high resolution, but it will be affected by the electrostatic force of the probe tip during the test. Optical second harmonic generation (SHG) detection technology is a non-contact, non-destructive all-optical detection technology that is not affected by factors such as electrostatic force and leakage current, and is easy to obtain the intrinsic polarization information of ferroelectric samples. At the same time, SHG technology has high sensitivity and has unique advantages in detecting the domain structure of samples with weak polarization signals. Prior art CN 117664925 A discloses an electrostatic voltage SHG test method. The electrostatic voltage SHG test technology is to apply a stable voltage while testing the SHG signal to test the change of the SHG signal with the voltage. Compared with the macroscopic hysteresis loop test, the electrostatic voltage SHG test technology can remove the influence of the leakage current factor during the test and obtain the change of the intrinsic ferroelectric polarization with the electric field. However, it takes several minutes to more than ten minutes for the electrostatic voltage SHG test technology to perform a voltage cycle test. The test time is too long, which makes it easier for external conditions to affect the energy, position and focusing state of the laser, thereby causing abnormal jitter and poor repeatability of the test data points. In addition, the ferroelectric material flipping time is extremely short, and the test method of applying electrostatic voltage cannot accurately show the polarization characteristics of the ferroelectric material itself. Therefore, how to achieve rapid testing of SHG signals under in-situ electric fields, reduce or eliminate the influence of external conditions, and better characterize the polarization characteristics of ferroelectric materials is a technical problem that technical personnel in this field urgently need to solve when using SHG to test ferroelectric devices. Summary of the invention In view of this, the present invention aims to solve the problems that static voltage SHG testing takes too long and is greatly affected by external conditions. In order to better characterize the polarization characteristics of ferroelectric materials, an in-situ AC voltage SHG system for improving the test speed and a method for characterizing intrinsic ferroelectric reversal are provided. The present invention uses a chopper to generate periodic light as a carrier signal, an arbitrary signal generator (AWG) to generate an AC voltage signal, and the SHG signal generated by the AC voltage signal acting on the sample is used as a modulation signal to achieve amplitude modulation of the optical signal, and the PMT photoelectric detector (PMT) converts the modulated optical signal into an electrical signal. The photoelectric signal of the PMT photoelectric detector and the carrier signal are simultaneously input into a digital phase-locked amplifier and demodulated and output. The application of the AC voltage and the demodulation output of the PMT photoelectric signal are carried out simultaneously, and are realized by a trigger signal generated by the AWG. Compared with the static voltage test, this method can complete the test within 300ms. To achieve the above object, the present invention adopts the following technical solution: An in-situ alternating current voltage SHG system, comprising a femtosecond laser, a variable attenuator, a chopper, a Glan prism, a half-wave plate, a long-wave pass filter, a beam splitter, an objective lens, a sample, a probe, a lens, a band-pass filter, a PMT photodetector, a control system, an arbitrary signal generator and a digital lock-in amplifier; Wherein, the Glan prism includes a first Glan prism and a second Glan prism; The incident side of the beam splitter prism is provided with a femtosecond laser, a variable attenuator, a chopper, a first Glan prism, a half-wave plate and a long-wave pass filter in sequence from far to near; The objective lens is arranged on the first light-splitting light-emitting side of the beam splitter prism, and the lens, the second Glan prism, the bandpass filter and the PMT photodetector are arranged in sequence from near to far on the second light-splitting light-emitting side of the beam splitter prism, the first light-splitting light-emitting side is 90° vertical along the clockwise direction of the light-incident side of the beam splitter prism, and the second light-splitting light-emitting side is opposite to the first light-splitting light-emitting side; The sample is vertically arranged at the bottom of the objective lens; the top of the probe is connected to the sample, and the probe is electrically connected to the arbitrary signal generator; The chopper is electrically connected to the digital lock-in amplifier, and the PMT photodetector is electrically connected to the digital lock-in amplifier; The arbitrary signal generator and the digital phase-locked amplifier are electrically connected to the control system respectively, and the trigger signal output end of the arbitrary signal generator is electrically connected to the trigger signal input end of the digital phase-locked generator. Further, the in-situ AC voltage SHG system also includes a reflector; The reflector comprises a first reflector and a second reflector; The first reflector is disposed between the variable attenuator and the chopper, the chopper is located obliquely below the left side of the variable attenuator, and the first reflector is used to refract the laser light passing through the variable attenuator by 90° and pass through the chopper; The second reflector is arranged between the first Glan prism and the half wave plate, and the half wave plate is located obliquely below the right side of the first Glan prism. The second reflector is used to refract the laser passing through the first Glan prism by 90° and pass it through the half wave plate. Further, the sample is a ferroelectric thin film sample or a transistor device sample; The ferroelectric thin film sample includes a substrate, a bottom electrode, a ferroelectric layer, and a top electrode from bottom to top, and the transistor device sample includes a substrate, a bottom electrode, a gate dielectric layer, a channel layer, and a top electrode from bottom to top; There are two probes, and the two probes are respectively connected to the top electrode and the bottom electrode of the sample. The present invention also provides a method for characterizing intrinsic ferroelectric switching using the above-mentioned in-situ AC voltage SHG system, comprising the following steps: (1) Preparation of ferroelectric thin films or transistor devices; (2) Connect the lines, connect the TTL signal of the chopper and the output signal of the PMT to the two input terminals of the digital phase-locked amplifier respectively; connect the output terminal of the AWG to the probe; connect the trigger signal output terminal of the AWG to the trigger signal input terminal of the digital phase-locked generator; (3) Set the waveform, frequency, amplitude and trigger signal of the pulse signal in the AWG; (4) Setting the demodulation parameters and the triggering mode of signal acquisition in the digital lock-in amplifier; (5) connecting two probes to the top electrode and bottom electrode of the sample respectively; applying pulsed laser to the sample vertically by a femtosecond laser, and focusing the pulsed laser on the surface of the ferroelectric thin film sample through the electrode through the objective lens or focusing on the channel next to the top electrode of the transistor device sample; (6) Applying an AC voltage to the sample and sending a trigger signal to control the phase-locked amplifier to collect data, completing the test of the device, and obtaining the curve of the ferroelectric layer SHG signal changing with the external electric field. In the scheme of the present invention, electric field application and data collection are performed simultaneously, and the entire test can be completed within 300ms. The trigger signal of the present invention controls voltage application and signal collection simultaneously. The present invention adopts a vertical optical path, and the generated SHG signal comes entirely from the in-plane signal of the sample, and the substrate, bottom electrode and top electrode do not generate SHG signals. Furthermore, the laser wavelength of the femtosecond laser is 800nm. Furthermore, the model of the AWG used in the present invention is Zurich UHF-AWG 600MHz, and the model of the digital lock-in amplifier is Zurich HF2Li 50MHz. Furthermore, the AC voltage is a triangular wave voltage. Preferably, in the above step (3), the waveform, phase, DC bias, amplitude, frequency and trigger signal of the voltage signal are set in the AWG, the phase, DC bias and amplitude correspond to the voltage required to be applied to the sample, an external voltage amplifier is selected when the range is exceeded, the frequency is related to the chopper frequency and the demodulation parameter tc, a cycle time is set to more than 300ms, the trigger signal is set by the market or trigger command, the AC voltage is set to 1 from the beginning to the end, and is set to 0 at other times. Preferably, in the above step (4), the demodulation parameters and the trigger mode of signal acquisition are set in the digital lock-in amplifier, wherein the demodulation parameter setting is related to noise, sample signal, etc., the filter order is set to 3-4 order, 1-2 order can be selected if the signal is particularly strong, and the parameter tc is 2-10 carrier cycles; the trigger mode of signal acquisition is set to the trigger signal input port name in the DAQ module, such as DIO, DIO1, etc. Furthermore, the ferroelectric layer is PbZr 0.2 Ti 0.8 O 3 Ferroelectric materials. Furthermore, the preparation method of the ferroelectric thin film sample is: A bottom electrode is deposited on the substrate by laser pulse deposition, and then a ferroelectric film is deposited on the bottom electrode. Then, a top electrode is deposited on the ferroelectric film by a mask, so as to obtain a ferroelectric film sample. The transistor device sample is a negative capacitance transistor device, and the preparation method of the transistor device sample is: A bottom electrode is deposited on the substrate by laser pulse deposition, and then a gate dielectric layer composed of a dielectric layer and a ferroelectric film is deposited on the bottom electrode. Then, a layer of two-dimensional material is transferred above the gate dielectric layer as a channel layer, and a top electrode is prepared on the channel layer by photolithography and evaporation to obtain a transistor sample. Furthermore, the bottom electrode is SRO, and the deposition conditions are a temperature of 690° C., an oxygen pressure of 80 mTorr, a laser energy of 380 mJ, and a focal length of 10. Furthermore, the ferroelectric film is PZT, the deposition temperature is 600° C., the oxygen pressure is 200 mTorr, the laser energy is 340 mJ, and the focal length is -10. The structure of the gate dielectric layer is STO / PZT / STO, the deposition temperature is 600° C., the oxygen pressure is 200 mTorr, the laser energy is 340 mJ, and the focal length is -10. Preferably, the PZT orientation is (001) or (111). Furthermore, the top electrode is ITO, the deposition temperature is 400° C., the oxygen pressure is 5 mTorr, the laser energy is 330 mJ, and the focal length is 10. Furthermore, the channel layer is a two-dimensional MoS 2 . The beneficial effects of the present invention are: the present invention solves the problem that the static voltage SHG test takes a long time and is greatly affected by the outside world, and can better characterize the polarization characteristics of ferroelectric materials. The present invention can be used to characterize the in-situ optical second harmonic of intrinsic ferroelectric reversal under AC voltage. The method of the present invention is a supplement to the fast testing direction of the in-situ static voltage SHG test technology, and at the same time reduces the influence of external conditions on the test results during the test (such as laser point drift, long-term irradiation causing sample damage, etc.), improves the test efficiency, and can better characterize the polarization characteristics of ferroelectric materials. BRIEF DESCRIPTION OF THE DRAWINGS Figure 1 This is a diagram of the damage to the sample caused by long-term laser irradiation and a diagram of the movement of the laser point before and after the test; Figure 2 It is a sample structure diagram in the present invention; Attached Figure 2 In the figure, the structures indicated by the reference numerals are as follows: 01 - substrate, 02 - bottom electrode, 03 - dielectric layer, 04 - ferroelectric layer, 05 - channel layer, 06 - top electrode. Figure 3 This is a conventional macroscopic polarization test diagram of a ferroelectric thin film sample in an embodiment of the present invention; Figure 4 It is a schematic diagram of the structure of the in-situ AC voltage SHG system with an external electric field in the present invention; Attached Figure 4 In the figure, the structures shown by the labels are as follows: 1-Femtosecond laser, 2-Variable attenuator, 3-Mirror, 4-Chopper, 5-Glan prism, 6-Half wave plate, 7-Long wave pass filter, 8-Beam splitter, 9-Objective lens, 10-Sample, 11-Probe, 12-Lens, 13-Band pass filter, 14-PMT photodetector, 15-Control system, 16-Arbitrary signal generator, 17-Digital lock-in amplifier. Figure 5 This is a graph showing the in-situ electrostatic voltage SHG test results of ferroelectric thin film samples with different orientations in an embodiment of the present invention; Figure 6 This is a graph showing the in-situ AC voltage SHG test results of ferroelectric thin film samples with different orientations in an embodiment of the present invention; Figure 7 Graph showing the test results of static voltage and AC voltage of a negative capacitance transistor sample in an embodiment of the present invention. DETAILED DESCRIPTION The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. In the description of the present invention, it is necessary to understand that the terms "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", etc., indicating the orientation or position relationship are based on the orientation or position relationship shown in the drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention. In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined. In the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances. In the present invention, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may include that the first and second features are in direct contact, or may include that the first and second features are not in direct contact but are in contact through another feature between them. Moreover, a first feature being "above", "above" and "above" a second feature includes that the first feature is directly above and obliquely above the second feature, or simply indicates that the first feature is higher in level than the second feature. A first feature being "below", "below" and "below" a second feature includes that the first feature is directly below and obliquely below the second feature, or simply indicates that the first feature is lower in level than the second feature. An in-situ alternating voltage SHG system, characterized in that the in-situ alternating voltage SHG system comprises a femtosecond laser 1, a variable attenuator 2, a chopper 4, a Glan prism 5, a half-wave plate 6, a long-wave pass filter 7, a beam splitter prism 8, an objective lens 9, a sample 10, a probe 11, a lens 12, a band-pass filter 13, a PMT photodetector 14, a control system 15, an arbitrary signal generator 16 and a digital lock-in amplifier 17; Wherein, the Glan prism 5 includes a first Glan prism and a second Glan prism; The light incident side of the beam splitter prism 8 is provided with a femtosecond laser 1, a variable attenuator 2, a chopper 4, a first Glan prism 5, a half-wave plate 6 and a long-wave filter 7 in order from far to near; The objective lens 9 is arranged on the first light-splitting light-emitting side of the beam splitter prism 8, and the lens 12, the second Glan prism 5, the band-pass filter 13 and the PMT photodetector 14 are arranged in sequence from near to far on the second light-splitting light-emitting side of the beam splitter prism 8, the first light-splitting light-emitting side is 90° vertical along the clockwise direction of the light-entering side of the beam splitter prism 8, and the second light-splitting light-emitting side is opposite to the first light-splitting light-emitting side; The sample 10 is vertically arranged at the bottom of the objective lens 9; the top of the probe 11 is connected to the sample, and the probe 11 is electrically connected to the arbitrary signal generator 16; The chopper 4 is electrically connected to the digital lock-in amplifier 17, and the PMT photodetector 14 is electrically connected to the digital lock-in amplifier 17; The arbitrary signal generator 16 and the digital phase-locked amplifier 17 are electrically connected to the control system 15 respectively, and the trigger signal output end of the arbitrary signal generator 16 is electrically connected to the trigger signal input end of the digital phase-locked generator 17 . In some embodiments, the in-situ AC voltage SHG system further comprises a reflector 3; The reflector 3 includes a first reflector and a second reflector; The first reflector is arranged between the variable attenuator 2 and the chopper 4. The chopper 4 is located obliquely below the left side of the variable attenuator 2. The first reflector is used to refract the laser light passing through the variable attenuator 2 by 90 degrees and pass through the chopper 4. The second reflector is arranged between the first Glan prism 5 and the half wave plate 6. The half wave plate 6 is located obliquely below the right side of the first Glan prism 5. The second reflector is used to refract the laser passing through the first Glan prism 5 by 90° and pass through the half wave plate 6. In some embodiments, the sample 10 is a ferroelectric thin film sample or a transistor device sample; The ferroelectric thin film sample includes substrate 01, bottom electrode 02, ferroelectric layer 04, and top electrode 06 from bottom to top, and the transistor device sample includes substrate 01, bottom electrode 02, gate dielectric layer (composed of dielectric layer 03 and ferroelectric layer 04), channel layer 05, and top electrode 06 from bottom to top; There are two probes 11 , and the two probes 11 are respectively connected to the top electrode 06 and the bottom electrode 01 of the sample 10 . In the embodiments of the present invention, PbZr with (001) and (111) orientations 0.2 Ti 0.8 O 3 Taking (PZT) ferroelectric film and negative capacitance transistor device containing (001) oriented PZT ferroelectric layer as examples, the in-situ optical second harmonic method of pulsed electric field to characterize the polarization of ferroelectric films and devices is explained and compared with the test under static voltage. Example 1 A method for preparing a ferroelectric thin film sample, wherein the preferred embodiment of the ferroelectric thin film of the present invention is PZT. like Figure 2 (a) is a schematic diagram of a ferroelectric thin film sample used for in-situ SHG testing in Example 1 of the present invention, wherein the ferroelectric thin film sample includes a substrate 01, a bottom electrode 02, a ferroelectric layer 04 and a top electrode 06; Figure 4 The optical path diagram of the SHG system of the present invention and the connection method of the characterization system are shown. A femtosecond laser emits a laser (1) with a wavelength of 800 nm. The laser energy is adjusted by a variable attenuator (2). The laser is converted into a periodic light of 1000 Hz by an optical chopper (4). The laser is then filtered into p-polarization (horizontally polarized light is defined as p-polarization) by a Glan prism (5). The polarization direction of the incident light is then changed by a half-wave plate (6). The laser below 700 nm is filtered out by a long-wave filter (7). The laser is then converted into a periodic light of 1000 Hz by a depolarizing beam splitter (8). The objective lens (9) is focused on the sample (10) through the transparent top electrode, and after exciting the 400nm second harmonic signal, it returns to the beam splitter prism along the original path with the 800nm ​​fundamental frequency light reflected by the sample surface mirror, and together with the laser, is focused through the lens (12), and the polarization direction of the signal to be extracted is selected through the Glan prism (5), and then the fundamental frequency light of 800nm ​​is filtered out through the bandpass filter (13) to avoid the influence of lasers in other bands on the final signal, and the remaining 400nm second harmonic signal is detected by the PMT photodetector (14). The parameter setting and data reading of the digital phase-locked amplifier and AWG are controlled by the labone program in the control system (15). The voltage signal is generated by the AWG (16), and two probes are connected through a BNC to alligator clip cable. One probe is placed on the top electrode irradiated by the laser (ferroelectric film sample) or the electrode next to the channel (negative capacitance device sample). The probe cannot block the laser spot, and the other end is connected to the silver paste led from the bottom electrode. While generating the voltage signal, the AWG also generates a trigger signal to be transmitted to the digital phase-locked amplifier (17) for synchronous signal acquisition to ensure that the SHG signal is detected in situ while applying the electric field, thereby reflecting the polarization information of the ferroelectric film or device. The method for preparing the ferroelectric thin film sample comprises the following steps: Pulsed laser deposition (PLD) was used to deposit (001) oriented SrTiO 3 A layer of SrRuO is first deposited on the STO substrate. 3 (SRO) bottom electrode, the preparation parameters of the SRO bottom electrode are as follows: temperature of 690°C, oxygen pressure of 80mTorr, laser energy of 380mJ, focal length of 10, and thickness of 25nm, and then a PZT ferroelectric thin film is deposited on the SRO bottom electrode. The deposition parameters of the PZT ferroelectric thin film are temperature of 600°C, oxygen pressure of 200mTorr, laser energy of 340mJ, focal length of -10, and thickness of 140nm. Finally, a transparent indium tin oxide (ITO) top electrode with a diameter of 100μm is deposited on the surface of the PZT film using a metal mask. The deposition temperature of the ITO transparent electrode is 400°C, oxygen pressure of 5mTorr, laser energy of 330mJ, focal length of 10, and thickness of 200nm. This embodiment uses PZT as an example of a ferroelectric thin film sample, but the ferroelectric thin film sample used in the embodiment can also be made of other ferroelectric materials such as barium titanate (BTO), lead titanate (PTO), etc.; at the same time, it can also be measured using an in-situ AC voltage SHG system to obtain a better SHG flip loop, thereby realizing the characterization of intrinsic ferroelectric flipping under voltage. Example 2 A method for preparing a ferroelectric thin film sample is different from Example 1 in that a (111) oriented STO substrate is selected to prepare a (111) oriented PZT thin film. Example 3

[0001] Preparation method of PZT negative capacitance transistor device sample: firstly deposit a layer of SRO bottom gate electrode on (001) oriented STO substrate by laser pulse deposition (PLD), and the preparation parameters of SRO bottom gate electrode are as follows: temperature of 690℃, oxygen pressure of 80mTorr, laser energy of 380mJ, focal length of 10, thickness of 25nm, and then prepare STO / PZT / STO gate dielectric layer on SRO bottom gate electrode, and the preparation parameters of STO / PZT / STO gate dielectric layer are as follows: temperature of 600℃, oxygen pressure of 200mTorr, laser energy of 340mJ, focal length of -10, thickness of 160nm; then transfer 3nm thick MoS on STO / PZT / STO gate dielectric layer by two-dimensional transfer stage 2 Finally, micro-nano processing and electron beam evaporation were used to deposit MoS 2 Ti / Au source and drain electrodes were prepared on the substrate. This embodiment is described with Ti / Au source and drain electrodes, but other conductive materials such as ITO, graphene and other transparent conductive materials can also be selected in this embodiment; in addition, this embodiment is described with negative capacitance transistor devices, but other transistor structures with gate dielectric layers can also be selected in this embodiment, such as STO / PZT with different proportions, pure PZT and other gate dielectric layers; at the same time, it can also be measured using an in-situ AC voltage SHG system to obtain a better SHG curve and realize the characterization of intrinsic ferroelectric reversal under voltage. In the present invention, due to the graphene and MoS 2 The two-dimensional stacked structure is easier to be laser ablated and is suitable for samples that can be tested with lower laser energy. Example 4 The difference from Example 1 is that the (001) oriented PZT thin film sample is tested using a conventional polarization measurement method for characterizing polarization reversal. Example 5 The difference from Example 1 is that the (111) oriented PZT thin film sample is tested using a conventional polarization measurement method to characterize polarization reversal. Figure 3 is the conventional macroscopic polarization test result of Examples 4 and 5, wherein Figure 3 (a) and Figure 3 (c) is the macroscopic hysteresis loop test result. Figure 3 (b) and Figure 3 (d) is the leakage current test result. It can be seen that the two PZT ferroelectric thin film samples have serious leakage current and cannot be effectively polarized by traditional polarization. Example 6 The difference from Example 1 is that the intrinsic ferroelectric switching is characterized by an in-situ static voltage SHG test system, that is, a fixed DC voltage is applied by a voltage source to test the SHG signal of the sample, and then the DC voltage value is changed for cyclic testing, with a voltage change step of 0.2V, ranging from 0V to 6V to -6V to 0V. Example 7 The difference from Example 2 is that the intrinsic ferroelectric switching is characterized by an in-situ static voltage SHG test system, that is, a fixed DC voltage is applied by a voltage source to test the SHG signal of the sample, and then the DC voltage value is changed to perform a voltage cycle test, with a voltage change step of 0.4V, ranging from 0V to 10V to -10V to 0V. Figure 5 This is a graph showing the electrostatic voltage test results of a ferroelectric thin film sample in an embodiment of the present invention, wherein: Figure 5 (a) is a curve of the SHG signal intensity of the (001) oriented PZT ferroelectric thin film sample (ie, Example 6) versus applied voltage. It can be seen that when the leakage current is large, the intrinsic ferroelectric polarization of the ferroelectric film can still be characterized by the in-situ electrostatic voltage SHG test system. Figure 5 (b) is a curve showing the variation of SHG signal intensity with applied voltage for the (111) oriented PZT ferroelectric thin film sample (ie, Example 7). This sample can also characterize the intrinsic ferroelectric polarization when the leakage current is relatively large. However, in actual use, it was found that this static voltage test method takes too long (10 to 20 minutes), and is easily affected by external conditions during the test, resulting in jump points and an overall decrease in signal strength. In addition, long-term testing results in a large difference in the signal before and after the sample test, which can be alleviated through multiple cycles, but the time cost is high. And because the test is conducted under quasi-static conditions, the hysteresis of the curve obtained by the test is small, which is quite different from the actual use of the device. Example 8 A method for characterizing intrinsic ferroelectric switching using an in-situ AC voltage SHG test system comprises the following steps: S1 was deposited on SrTiO with orientation (001) by pulsed laser deposition (PLD). 3 A layer of SrRuO is deposited on the STO substrate 3(SRO) bottom electrode, the preparation parameters of the SRO bottom electrode are as follows: temperature of 690°C, oxygen pressure of 80mTorr, laser energy of 380mJ, focal length of 10, and thickness of 25nm; then a PZT ferroelectric thin film is deposited on the SRO bottom electrode, and the preparation parameters of the PZT ferroelectric thin film are temperature of 600°C, oxygen pressure of 200mTorr, laser energy of 340mJ, focal length of -10, and thickness of 140nm. Finally, a transparent indium tin oxide (ITO) top electrode with a diameter of 100μm is deposited on the surface of the PZT film using a metal mask. The deposition temperature of the ITO transparent electrode is 400°C, oxygen pressure of 5mTorr, laser energy of 330mJ, focal length of 10, and thickness of 200nm. S2 connects the TTL signal of the chopper and the photoelectric output signal of the PMT to the two input terminals of the digital phase-locked amplifier respectively; connects the output terminal of the AWG to the probe; connects the trigger signal output terminal of the AWG to the DIO 1 signal input terminal of the digital phase-locked generator; S3 outputs a triangular wave voltage of one cycle through AWG, with an amplitude of 6V, no DC offset, no phase offset, sampling point 64000Sa, and sampling frequency 219.72kSa / s. When AWG outputs the triangular wave, a trigger signal is generated through the marker command to trigger the synchronous signal acquisition of the digital lock-in amplifier; The demodulation parameters of the S4 digital lock-in amplifier are 4th order filtering, the filtering parameter tc is 5.082ms, the sampling frequency is 14.39kSa / s, and the trigger mode is changed to DIO 1 signal trigger; S5 connects the two probes to the top electrode and bottom electrode of the sample respectively; applies pulsed laser vertically to the sample along the optical path, with a laser power of 15mW, and the pulsed laser is focused on the surface of the ferroelectric film through the objective lens and the transparent electrode; S6, by applying a triangular wave voltage on the gate and substrate through the AWG and sending a trigger signal to control the phase-locked amplifier to collect data, the device is tested and the curve of the SHG signal of the ferroelectric layer changing with the applied electric field is obtained. The time lag is t = 3.9tc, and the sampling point corresponding to the triangular wave voltage is calculated according to the sampling frequency of the digital phase-locked amplifier to obtain the curve of the SHG signal intensity changing with the voltage. Figure 6 (a) is the in-situ AC voltage SHG test result of Example 8 of the present invention. Compared with the static voltage test result (Example 6), the two have the same trend and shape, but the hysteresis effect is quite different. In addition, the curve is smoother, the hysteresis effect is better, and it is closer to the actual working state of the device. Moreover, the test time is shorter, and a large number of tests can be performed in a short time, reducing the influence of external factors on the test. Similarly, based on the ferroelectric thin film sample prepared in Example 2, Example 9 was set up. Example 9 A method for characterizing intrinsic ferroelectric switching using an in-situ AC voltage SHG test system, which differs from Example 8 in that the ferroelectric film is (111) oriented and the amplitude is 10V. Figure 6 (b) is the test result of Example 9. Compared with the test result of Example 7, the hysteresis effect is better, it can better reflect the ferroelectric layer switching effect, the test is faster, and it is less affected by the outside world. In order to test the effect of using the characterization method in a device, based on Example 3, static voltage and AC voltage were applied respectively to characterize the SHG signal intensity to set up Examples 10 and 11. Example 10 The intrinsic ferroelectric reversal of the ferroelectric layer of the negative capacitance transistor is characterized by an in-situ static voltage SHG signal test system. Compared with Example 6, the laser focus position is changed to the channel next to the top electrode, starting from -2V with a step size of 0.02V, and other conditions remain unchanged. Figure 7 (a) is the test result of the present embodiment. The test curve shows that the curve is nearly parallel under negative voltage, and the flip phenomenon occurs under positive voltage, which conforms to the ferroelectric layering state of this negative capacitance transistor device that varies with voltage. However, the negative capacitance transistor test requires a smaller step length, so it takes more than 2 times the time of the normal ferroelectric film test, and is more susceptible to external conditions. As shown in the figure, the jump point causes the SHG signal intensity after the jump point to shift downward as a whole, affecting the analysis of the actual curve shape. Embodiment 11 The intrinsic ferroelectric switching of the ferroelectric layer of the negative capacitance transistor is characterized by an in-situ AC voltage SHG signal test system. Compared with Example 8, the difference is that the laser focus position is changed to the channel next to the top electrode, the amplitude is changed to 2V, and the phase starts from -2V. Figure 7 (b) is the test result of this embodiment. The test curve is basically similar to that of embodiment 10, but smoother. There is ferroelectric polarization hysteresis at positive voltage, and no flip phenomenon occurs at negative voltage. Moreover, in the positive voltage part, the slope of the rising and falling lines is less changed than that of embodiment 10, and there is a small amount of hysteresis. Examples 6-7 and 8-9 show that the ferroelectric thin film samples are prone to various problems when using in-situ static voltage to test the SHG signal. The in-situ AC voltage proposed in the present invention can eliminate or reduce the influence of external conditions on the test results. Examples 10 and 11 show that not only ferroelectric thin film samples, but also ferroelectric devices can be tested by this method. In summary, the present invention provides a method for characterizing intrinsic ferroelectric reversal using an in-situ AC voltage SHG system. This method can be applied to ferroelectric thin films and transistor devices, and is a supplement to the static voltage SHG test method. It can eliminate or reduce external problems caused by long-term testing. The method is applicable to ferroelectric material systems and can be used to quickly characterize a large number of ferroelectric devices. The present invention is of great significance for in-depth understanding of ferroelectric materials, exploration of intrinsic polarization of ferroelectric devices, and promotion of the use of ferroelectric negative capacitance devices. Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. An in-situ AC voltage SHG system, characterized in that: The in-situ AC voltage SHG system includes a femtosecond laser, a variable attenuator, a chopper, a Glan prism, a half-wave plate, a long-wave pass filter, a beam splitter, an objective lens, a sample, a probe, a lens, a band-pass filter, a PMT photodetector, a control system, an arbitrary signal generator and a digital lock-in amplifier; Wherein, the Glan prism includes a first Glan prism and a second Glan prism; The incident side of the beam splitter prism is provided with a femtosecond laser, a variable attenuator, a chopper, a first Glan prism, a half-wave plate and a long-wave pass filter in sequence from far to near; The objective lens is arranged on the first light-splitting light-emitting side of the beam splitter prism, and the lens, the second Glan prism, the bandpass filter and the PMT photodetector are arranged in sequence from near to far on the second light-splitting light-emitting side of the beam splitter prism, the first light-splitting light-emitting side is 90° vertical along the clockwise direction of the light-incident side of the beam splitter prism, and the second light-splitting light-emitting side is opposite to the first light-splitting light-emitting side; The sample is vertically arranged at the bottom of the objective lens; the top of the probe is connected to the sample, and the probe is electrically connected to the arbitrary signal generator; The chopper is electrically connected to the digital lock-in amplifier, and the PMT photodetector is electrically connected to the digital lock-in amplifier; The arbitrary signal generator and the digital phase-locked amplifier are electrically connected to the control system respectively, and the trigger signal output end of the arbitrary signal generator is electrically connected to the trigger signal input end of the digital phase-locked generator.

2. The in-situ AC voltage SHG system according to claim 1, characterized in that: Also includes reflectors; The reflector comprises a first reflector and a second reflector; The first reflector is disposed between the variable attenuator and the chopper, the chopper is located obliquely below the left side of the variable attenuator, and the first reflector is used to refract the laser light passing through the variable attenuator by 90° and pass through the chopper; The second reflector is arranged between the first Glan prism and the half wave plate, and the half wave plate is located obliquely below the right side of the first Glan prism. The second reflector is used to refract the laser passing through the first Glan prism by 90° and pass it through the half wave plate.

3. The in-situ AC voltage SHG system according to claim 1, characterized in that: The sample is a ferroelectric thin film sample or a transistor device sample; The ferroelectric thin film sample includes a substrate, a bottom electrode, a ferroelectric layer, and a top electrode from bottom to top, and the transistor device sample includes a substrate, a bottom electrode, a gate dielectric layer, a channel layer, and a top electrode from bottom to top; There are two probes, and the two probes are respectively connected to the top electrode and the bottom electrode of the sample.

4. A method for characterizing intrinsic ferroelectric switching using the in-situ AC voltage SHG system according to any one of claims 1 to 3, characterized in that: The following steps are involved: A femtosecond laser is used to apply pulsed laser vertically to the sample. The pulsed laser passes through the objective lens through the electrode and is focused on the surface of the ferroelectric thin film sample or on the channel next to the top electrode of the transistor device sample. Then, an AC voltage is applied to the sample and a trigger signal is sent to control a digital phase-locked amplifier to collect data, thereby completing the test of the device and obtaining a curve of the SHG signal of the ferroelectric layer changing with the applied electric field.

5. The method for characterizing intrinsic ferroelectric switching using an in-situ AC voltage SHG system according to claim 4, characterized in that: The AC voltage is a triangular wave voltage.

6. The method of characterizing intrinsic ferroelectric switching using an in-situ AC voltage SHG system according to claim 4, characterized in that: The ferroelectric layer is PbZr 0.2 Ti 0.8 O3 ferroelectric material.

7. The method of characterizing intrinsic ferroelectric switching using an in-situ AC voltage SHG system according to claim 4, characterized in that: The preparation method of the transistor device sample is as follows: A bottom electrode is deposited on the substrate by laser pulse deposition, and then a gate dielectric layer composed of a dielectric layer and a ferroelectric film is deposited on the bottom electrode. Then, a layer of two-dimensional material is transferred above the gate dielectric layer as a channel layer, and a top electrode is prepared on the channel layer by photolithography and evaporation to obtain a transistor sample.

8. The method for characterizing intrinsic ferroelectric switching using an in-situ AC voltage SHG system according to claim 7, characterized in that: The bottom electrode is SRO, and the deposition conditions are: temperature of 690° C., oxygen pressure of 80 mTorr, laser energy of 380 mJ, and focal length of 10.

9. The method of characterizing intrinsic ferroelectric switching using an in-situ AC voltage SHG system according to claim 7, characterized in that: The structure of the gate dielectric layer is STO / PZT / STO, the deposition temperature is 600° C., the oxygen pressure is 200 mTorr, the laser energy is 340 mJ, and the focal length is -10.

10. The method for characterizing intrinsic ferroelectric switching using an in-situ AC voltage SHG system according to claim 7, characterized in that: The channel layer is two-dimensional MoS2.

Citation Information

Patent Citations

  • Method for representing intrinsic ferroelectric upset by using in-situ electric field SHG system

    CN117664925A

  • Joint test system of macro / micro structure and electrical performance of ferroelectric film

    CN109884346A

  • Second harmonic generation (SHG) optical inspection system designs

    CN113167741A

  • Device and method for measuring carrier lifetime of two-dimensional semiconductor material

    CN114002157A

  • Method for testing suspended two-dimensional ferroelectric material by using optical second harmonic

    CN116448726A